1998
DOI: 10.1086/305076
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Orion Nebula Cluster Structure and Dynamics

Abstract: We use optical and near-infrared star counts to explore the structure and dynamics of the Orion Nebula Cluster (ONC). This very young (\1 Myr) cluster is not circularly symmetric in projection but is elongated north-south in a manner similar to the molecular gas distribution in the region, suggesting that the stellar system may still reÑect the geometry of the protocluster cloud. Azimuthally averaged stellar source counts compare well with simple spherically symmetric, single-mass King cluster models. The mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
792
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 669 publications
(865 citation statements)
references
References 38 publications
68
792
3
2
Order By: Relevance
“…Hillenbrand (1997) finds evidence for mass segregation in the more evolved ONC with the most massive stars preferentially located within projected radii of <0.3 pc. In a later paper Hillenbrand & Hartmann (1998) find that this distribution of stars is unlikely to be the result of dynamical mass segregation since its timescale is larger than the age of the ONC stars. The authors instead favour a primordial origin of the observed mass segregation.…”
Section: The Future Of Sdc335mentioning
confidence: 86%
“…Hillenbrand (1997) finds evidence for mass segregation in the more evolved ONC with the most massive stars preferentially located within projected radii of <0.3 pc. In a later paper Hillenbrand & Hartmann (1998) find that this distribution of stars is unlikely to be the result of dynamical mass segregation since its timescale is larger than the age of the ONC stars. The authors instead favour a primordial origin of the observed mass segregation.…”
Section: The Future Of Sdc335mentioning
confidence: 86%
“…Some authors (e.g., Parenago 1954;Strand 1958;Fallon et al 1977) have claimed evidence of expansion or contraction, but it has also been claimed that these results are due to observational errors (e.g., Vasilevskis 1962Vasilevskis , 1971Allen et al 1974). Furthermore, given the velocity dispersions, one would expect the ONC core to be virialized and not contracting nor expanding motions are expected (e.g., Hillenbrand & Hartmann 1998).…”
Section: The Internal Kinematicsmentioning
confidence: 99%
“…In the core of the ONC (Hillenbrand & Hartmann 1998), there are two sub-regions of particular interest: the Orion Trapezium and the Orion BN/KL region, which is located behind the ONC. Together they cover an area of a few square arcminutes.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that the most massive stars are concentrated towards the center of the cluster is observed in many more young clusters (Hillenbrand & Hartmann 1998;Gouliermis et al 2004). Mass segregation to the center of the cluster could be primordial or dynamical: the most massive stars can be concentrated at or near the center or migrate into the center of the cluster due to two-body interactions.…”
Section: Discussionmentioning
confidence: 99%